2022
DOI: 10.9734/psij/2022/v26i9-10762
|View full text |Cite
|
Sign up to set email alerts
|

Study of Compact Stars with Buchdahl Potential in 5-D Einstein-Gauss-Bonnet Gravity

Abstract: The general theory of relativity has allowed a better understanding of the structure of universe. One of the fundamentals problems in the general relativity is finding exact solutions of the Einstein-Maxwell field equations. Some solutions found applications in astrophysics, cosmology and more recently in the developments inspired by string theory. In this paper, we presented a compact object model in the framework of Einstein-Gauss-Bonnet gravity (EGB) with a linear equation of state considering a metric pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Gage cursory look of Algorithm (I) and Algorithm (II) will tell us that while electromagnetic force appears as signal profile field matrix, gravitational force appears as density matrix time space manifesting flavor with mass factor, and both together in stringmetrics. 1,[4][5][6][7]9,10,11,16,18 Practically achieving with typically observations measurements having spectral density alongside intensities signal profiling will be then part of experimental physics.…”
Section: Algorithm (Ii)mentioning
confidence: 99%
See 1 more Smart Citation
“…Gage cursory look of Algorithm (I) and Algorithm (II) will tell us that while electromagnetic force appears as signal profile field matrix, gravitational force appears as density matrix time space manifesting flavor with mass factor, and both together in stringmetrics. 1,[4][5][6][7]9,10,11,16,18 Practically achieving with typically observations measurements having spectral density alongside intensities signal profiling will be then part of experimental physics.…”
Section: Algorithm (Ii)mentioning
confidence: 99%
“…Hod-PDP circuit assembly dynamically progressively stabilizes through quantum level creation from Superluminous Plenum generating energy perpetually while keeping "zitterbewegung", average universal temperature, gravitational waves, and cosmic microwave background by having critical signal/noise density matrix evolving out of observables Algorithm Equation (I). [9][10][11][12][13][14][15][16][17][18] We get the whole picture by computer simulation matrix programming problem solving simultaneously Algorithm (I) & Algorithm (II) to get proper observables that are experimentally testable observations measurable parameters grand unifying physics! !Algebra gage theory discontinuum dissipative physical mathematical sciences paradigm shifting quantum relativity has proved to be main key to achieving it!!…”
Section: Algorithm (Ii)mentioning
confidence: 99%
“…[69][70][71] Now by setting k = 0 we can reduce GCG and also cosmological constant type dark energy EOS can be described under the specification n = −1 and h = 1 + k. Recently, many stable and viable models on physical characteristics of compact objects have been developed by using MCG EOS. [72][73][74][75][76][77] Based on the above background, the main motivation behind the choice of MCG for our study is to emphasize the effect of MCG on various physical attributes of a spherically symmetric dark energy stars. The rest of the paper is organised as follows : In Section 2, we have formulated the Einstein-Maxwell field equa-tions for a mixture of ordinary and dark matter fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Tello-Ortiz et al (2020) found an anisotropic fluid sphere solution of the Einstein-Maxwell field equations with a modified Chaplygin equation of state. More recently, Malaver et al (2022) obtained new solutions of Einstein's field equations in a Buchdahl spacetime considering a nonlinear electromagnetic field.…”
Section: Introductionmentioning
confidence: 99%